Arteriovenous fistulas for hemodialysis in patients suffering from chronic renal failure: our experience as regards difficulties and complications - Nagi, Gurinderjit Singh; Multani, Jangpreet Singh; Arora, Rajiv (International Surgery Journal, 2016)
Background: The study was conducted to assess the various complications which are encountered while creating arteriovenous fistula and post operatively during the period when fistula matures. Also the study was intended to study the failure rate and the importance of physical examination to assess vessel caliber clinically. Methods: The study comprised of 83 patients suffering from chonic renal failure and requied arteriovenous fistula for carrying out hemodialysis. The arteriovenous fistulas were created under local anesthesia, observing all precautions and end to side anastomosis was made after dissecting the vein and the artery. Results: The most common difficulty encountered at surgery was when cephalic vein was of very small caliber and we had to give a small longitudinal incision in the wall of vein or do cheatle manouvre to make the anastomosis adequate. In five cases we started for radiocephalic fistula but had to convert to brachiocepphalic fistule as arteriovenous anstomoosis was not possible between the radial artery and the cephalic vein. There were no major complications except redness and inflamation in five cases and pus formation in one case. Inflamation subsided with higher antibiotics and pus had to be drained resulting in satisfactory recovery.Most of the fistulas started well with good thrill and by the end of one month 69 out 83 arteriovenous fistulas were functioning well with a patency rate of 83.13%. Conclusions: There are no major complications after creating arteriovenous fistula and it is imperitive to do physical examination preoperatively to assess the vessel wall. In doubtful cases color Doppler may be got done for this. Postoperative precautions need to be observed for maturation of AV fistula.